Prostaglandin EP4 Selective Agonist AKDS001 Enhances New Bone Formation by Minimodeling in a Rat Heterotopic Xenograft Model of Human Bone - Ukon, Yuichiro; Nishida, Masahiro; Yamamori, Natsumi; Takeyama, Kazuhiro; Sakamoto, Kazuhito; Takenaka, Shota; Makino, Takahiro; Fujimori, Takahito; Sakai, Yusuke; Kanie, Yuya; Kodama, Joe; Bal, Zeynep; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
To enhance bone regeneration, the use of bone morphogenetic protein (BMP)-2 is an attractive option. Unfortunately, the dose-dependent side effects prevent its widespread use. Therefore, a novel osteogenic agent using a different mechanism of action than BMP-2 is highly desirable. Previous reports demonstrated that prostaglandin E2 receptor 4 (EP4) agonists have potent osteogenic effects on non-human cells and are one of the potential alternatives for BMP-2. Here, we investigated the effects of an EP4 agonist (AKDS001) on human cells with a rat heterotopic xenograft model of human bone. Bone formation in the xenograft model was significantly enhanced by AKDS001 treatment. Histomorphometric analysis showed that the mode of bone formation by AKDS001 was minimodeling rather than remodeling. In cultured human mesenchymal stem cells, AKDS001 enhanced osteogenic differentiation and mineralization via the cAMP/PKA pathway. In cultured human preosteoclasts, AKDS001 suppressed bone resorption by inhibiting differentiation into mature osteoclasts. Thus, we conclude that AKDS001 can enhance bone formation in grafted autogenous bone by minimodeling while maintaining the volume of grafted bone. The combined use of an EP4 agonist and autogenous bone grafting may be a novel treatment option to enhance bone regeneration. However, we should be careful in interpreting the results because male xenografts were implanted in male rats in the present study. It remains to be seen whether females can benefit from the positive effects of AKDS001 MS by using female xenografts implanted in female rats in clinically relevant animal models.